La cultura negociadora en el Perú: un estudio exploratorio - Ogliastri, Enrique (2008)
This is a qualitative study about how to conduct business in Peru. It is based on 47 semi-structured questionnaires on pointed negotiation experiences in which a Peruvian side was involved. The information was classified into 23 items about the customs, tactics, concepts, expectations, beliefs and values that occur in conflict and negotiation processes in Peru. Here was found a culture very similar to that widespread in Latin America: the dominance of haggling as a negotiating process, based on an unreasonable request at the beginning that is to be adjusted slowly. Cordial relations are preferred in an informal atmosphere; it is customary to not do much preparation for the negotiation and recourse to cunning and power more often than to objective technical criteria. In this culture emotions are expressed, and uncertainties have generated a great deal of flexibility in negotiations. The results must be validated by further analysis. This study is part of an extensive research on intercultural negotiation.